HUBUNGAN ANTARA MINAT DENGAN KEAKTIFAN BELAJAR WARGA BELAJAR PELATIHAN KETERAMPILAN ELEKTRONIKA PADA PSAABR BUDI UTAMA LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Putri Mulyasari (Universitas Negeri Padang, 2014)
This research is conducted based on the decrease of students' participation in learning elektronic workshop. Passion is one of factors that influences the students to participate in workshop. This research is aimed to describe the passion of students to participate in workshop. This research was correlational research. Research subject was 20 students that followed the electronic workshop in PSAABR Budi Utama Lubuk Alung Kabupaten Padang Pariaman. The result showed that there was a significant relationship between students' passion and activeness to participate in electronic workshop. It is suggented that the students should follow the activities based on their passion. The Instructor should attempt to omprove the students’ interest. The organizer should facilitate the appropriate workshop based on the students’ needs, interests, and talents.